2006
DOI: 10.1007/s10620-006-9131-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Digestive Tract Tumors in Down Syndrome: A Literature Review

Abstract: The purpose of this study was to describe the digestive neoplasms found in persons with Down syndrome. Due to intellectual disability, persons with Down syndrome do not convey their symptoms and pain, leading to delayed diagnosis and potentially worse outcome. It is thus important to know which organs are at risk for tumors and possible tumor risk factors. In a review of the literature, we found 13 benign tumors and 127 cancers in 1 fetus, 8 children, and 131 adults with Down syndrome. The review suggests a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…There is a suggestion that women with IDs are at higher risk than men [6,28,30], but there is a more mixed picture from the case studies. Interestingly, aside from the case studies, colon cancer was found in children with PWIDs [47,49]. Overall, findings indicate vigilance about colorectal cancer is needed when assessing the health or changes in behaviour in PWIDs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is a suggestion that women with IDs are at higher risk than men [6,28,30], but there is a more mixed picture from the case studies. Interestingly, aside from the case studies, colon cancer was found in children with PWIDs [47,49]. Overall, findings indicate vigilance about colorectal cancer is needed when assessing the health or changes in behaviour in PWIDs.…”
Section: Discussionmentioning
confidence: 97%
“…Two colorectal carcinoma cases have been reported in a neonate and a young adult with trisomy 13 [47], and such tumours were described in a female patient with tuberous sclerosis [48]. A literature review on individuals with Down syndrome and digestive cancer identified 39 colon cancers, but overall people with Down syndrome develop fewer digestive neoplasms compared to PWIDs [49]. In a Finnish data linkage study from a cancer registry of PWIDs (1982PWIDs ( -1986, 302 people with fragile-X syndrome were followed-up on cancer incidence until 2005 [50].…”
Section: Genetic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetics of bladder cancer do not point to chromosome 21 [19] . However, an overexpression of genes such as ANA, TIAM1, ETS2, IFNAR, COL18A1 and CAR has been suggested to exert a protective effect against various cancers [5,21,22] . ANA impairs serum-induced cell cycle progression from the G0/G1 to the S phase.…”
Section: Bladder Cancermentioning
confidence: 99%
“…Endostatin, the product of the COL18A1 gene, is a powerful antiangiogenic factor [for discussion, see ref. 5,21 ]. The coxsackie and adenovirus receptor gene which codes for a transmembrane protein involved in cellular adhesion is particularly expressed in urothelial tumors and is often downregulated in transitional cell carcinoma [22] .…”
Section: Bladder Cancermentioning
confidence: 99%